Current Therapeutic Advances Targeting EGFR and EGFRvIII in Glioblastoma - Padfield, Emily; Ellis, Hayley P.; Kurian, Kathreena M. (Frontiers in Oncology, 2015)
EGFR and EGFRvIII analysis is of current interest in glioblastoma- the most common malignant primary CNS tumour, because of new EGFRvIII vaccine trials underway. EGFR activation in glioblastoma promotes cellular proliferation via activation of MAPK and PI3K-Akt pathways and EGFRvIII is the most common variant, leading to constitutively active EGFR. This review explains EGFR and EGFRvIII signalling in GBM; describes targeted therapy approaches to date including tyrosine kinase inhibitor, antibody-based therapies, vaccines and preclinical RNA-based therapies and discusses the difficulties encountered with these approaches including pathway redundancy and intratumoural heterogeneity.